CHARACTERISTICS OF OPPORTUNISTIC BACTERIA OF MICROBIAL COMMUNITIES OF THE LENA RIVER ON THE DEGREE OF DOMINANCE AND DIVERSiTY - E. V. Anganova; E. D. Savilov; N. N. Chemezova; A. V. Duhkanina (Acta Biomedica Scientifica, 2012)
The results of the study of opportunistic bacteria of the Lena river are show in the article. The microbial community of the river is represented by bacteria of different families. Opportunistic Enterobacteriaceae is absolutely dominated. Enterobacteria of different type belonged to four classes of dominance. The fluctuations in the frequency of their occurrence did. not extend beyond the class for the period of observation. At the same time the changes in their populations at the level of diversity are identified.